The Pengaruh Karakteristik Dewan Direksi Terhadap Financial Distress: Pada Perusahaan BUMN di Indonesia Tahun 2015 – 2019 - Atikah Mauda; Vanica Serly (Universitas Negeri Padang, 2021)
The purpose of this study was to analyze the effect of directors remuneration, size of the board of directors , board of directors meeting frequency, profitability, and leverage on financial distress. The data in this study are annual reports of BUMN companies in Indonesia registered at the Ministry of BUMN in 2015 - 2019. The sampling method using purposive sampling method obtained by a sample of 110 companies. Testing the hypothesis in this study using multiple linear regression analysis. The results of his research are the directors remuneration, size of the board of directors has no effect on financial distress. Meanwhile, board of directors meeting frequency, profitability, and leverage affect financial distress.